The Distribution of Soil Micro-Nutrients and the Effects on Herbage Micro-Nutrient Uptake and Yield in Three Different Pasture Systems - Thomas, Cathy L.; Darch, Tegan; Harris, Paul; Beaumont, Deborah A.; Haefele, Stephan M. (Agronomy (Basel), 2021)
Pasture micro-nutrient concentrations are often deficient for herbage productivity and the health of livestock. The aim of this study was to investigate soil and herbage micro-nutrient content and the effects on yield on the three pasture systems of the North Wyke Farm Platform (NWFP): high-sugar grass + legume mix minus nitrogen (N) fertilizer (blue/HSG + L); permanent pasture plus N fertilizer (green/P + N); high-sugar grass plus N fertilizer (red/HSG + N). The locations with high soil total micro-nutrient concentrations had a greater slope and higher soil organic matter (SOM) content. Herbage micro-nutrient concentrations were often greater at the locations with high soil total micro-nutrient concentrations. The concentration and uptake of nearly all micro-nutrients was greatest in the herbage of the green/P + N system, which had the highest SOM content, whereas they were often lowest in the red/HSG + N system, which had the lowest SOM and the highest yield, indicating biomass dilution of micro-nutrients in the herbage. At the locations with high soil micro-nutrient concentrations, yield was higher than at locations with low micro-nutrient concentrations, and was equal across the three pasture systems, regardless of fertilizer N treatment. Variation in micro-nutrient uptake/yield in the blue grass–legume system was predominantly explained by the soil molybdenum (Mo) concentration, possibly relating to the requirement for Mo in biological nitrogen fixation. There was, therefore, a trade-off in ploughing and re-seeding for higher yield, with the maintenance of SOM being important for herbage micro-nutrient content.